The Effects of Capacity Building Program for Village Health Volunteers on Knowledge and Ability to Screen Elder Abuse in Community - Seesawang, Junjira; Thongtang, Pulawit (Nursing Science Journal of Thailand, 2023)
Purpose: To study the effects of a capacity building program for village health volunteers on knowledge and ability to screen elder abuse in community. Design: Quasi-experimental research design. Methods: Sixty village health volunteers were divided into the control and experimental group with 30 each who lived in a province of Thailand. The experimental group received the capacity building program for screening elder abuse based on participatory learning concept for 8 weeks which comprised elder abuse screening education and training, screening elder abuse in the community, assessment of village health volunteer working in community, and focus group discussion. Data were collected using a set of questions to assess elder abuse knowledge and ability to screen elder abuse before and after the program implemented. Data were analyzed using descriptive statistics and t-test. Main findings: The results revealed that the experimental group had higher scores of knowledge and ability regarding elder abuse screening at post program than that at pre-program (p < .001) and that in the control group (p < .001). Conclusion and recommendations: An appropriate knowledge and skill toward elder abuse and participatory learning could enhance village health volunteers’ knowledge and ability to perform elder abuse screening. Thus, nurse should increase accurate understanding and important skills toward elder abuse screening in community for village health volunteers by allowing them to participate in discussion, practice elder abuse screening and discuss the problem and suggestion after performing elder abuse screening.